Legal and illicit sand mining practice in Bangladesh: Exploring supply chain and its value - Estiaque Bari; Sarah Enamul Haque (Journal of Illicit Economies and Development (JIED), 2022)
The paper is one of the first attempts to explore and identify sand mining supply chain and its value in Bangladesh in the following three river basins: Meghna, Brahmaputra and Jinjiram. It also aims to stir interest in the topic for future research and provide policymakers a background evidence to take informed policy measures. To carry out the study a total of 266 questionnaire-based survey responses were collected from the local people and 40 key informant interviews (KIIs) were conducted with major stakeholders. The results of the study reveal that although sand mining is done illegally in the Brahmaputra river basin, the value addition per cubic feet of mined sand is comparable to that of the legal sand mining sites of the Meghna basin. In the Jinjiram basin, value addition is comparatively lower. Riverine people from smaller basins are deriving significantly higher economic benefits from sand mining activities and experiencing significantly lower incidences of river erosion than the people from larger river basins. Riverine communities of nearby legal sand mining sites perceive significantly less social conflict, improved water navigation, less incidences of embankment damage. In contrast to people residing nearby illegal sand mining sites, they are also more aware of the fact that government is losing significantly higher potential revenue from rampant extraction of sands from different river banks. The paper finally argued that after making proper environmental assessments and feasibility study government of Bangladesh should consider to provide legal permit to more sand mining sites and divert a portion of potential revenue earned from these additional permits to riverine communities to offset some of their future adaptation and mitigation costs.
Keywords: 330; Supply chains; Sand mining; Value addition; Community perceptions; River basin